Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1002/jsfa.10855
|View full text |Cite
|
Sign up to set email alerts
|

Dietary oleuropein extract supplementation and its combination with α‐tocopheryl acetate and selenium modifies the free fatty acid profile of pork and improves its stability

Abstract: BACKGROUND Olive‐derived antioxidants have been shown to affect the oxidative status of meat and have also been associated with greater consumption of glucose, which might affect glycogen stores and muscle characteristics. This study evaluated the effect of oleuropein extract supplementation (OLE) versus vitamin E + Se (VE), and their combination (VEOLE), in pig diets, on pH, drip loss, the proportion of free fatty acids, and meat stability, and their prediction by blood oxidative status markers. RESULTS The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…In the present study, no differences in ADWG, ADFI, or FCR were observed in pigs supplemented with the experimental diets and a lack of effects on lean or fat thickness of carcass yield was observed. Similar results have been reported through the single administration of vitamin E and/or oleuropein extract [6,30]. Other feed additives, such as magnesium, have been reported to improve the performance at 0.3% (3000 mg/kg) of MgO on the diets of swine over 7 days [31].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…In the present study, no differences in ADWG, ADFI, or FCR were observed in pigs supplemented with the experimental diets and a lack of effects on lean or fat thickness of carcass yield was observed. Similar results have been reported through the single administration of vitamin E and/or oleuropein extract [6,30]. Other feed additives, such as magnesium, have been reported to improve the performance at 0.3% (3000 mg/kg) of MgO on the diets of swine over 7 days [31].…”
Section: Discussionsupporting
confidence: 80%
“…Vitamin E is one of the most potent antioxidants in the organism that can be accumulated in muscle membranes, so a higher presence of this vitamin has been associated with lower TBARS production and higher lipid stability [9]. In addition, the use of oleuropein extract has been reported to delay lipid oxidation in meat from birds [30] and pork [6], and similar results have been found in pork through the use of olive leaves that may contain not only oleuropein but also other antioxidant components [45]. Lower TBARS values have also been observed in meat from pigs given a short-term feeding of magnesium supplements [46], although supplementation doses were much higher (1500 mg/kg) than those used in the present research.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations